2022
DOI: 10.1002/advs.202105672
|View full text |Cite
|
Sign up to set email alerts
|

HTR1A Inhibits the Progression of Triple‐Negative Breast Cancer via TGF‐β Canonical and Noncanonical Pathways

Abstract: Triple‐negative breast cancer is the most aggressive subtype of breast cancer and the incidence of depression in breast cancer patients is high, which leading to worse survival and increased risk of recurrence. The effect of antidepressants on breast cancer patients remains contradictory, which might be due to variations in antidepression targets. Therefore, there is significant value to explore the antitumor potential of antidepressants and discover new therapeutic targets for breast patients. The authors scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…To resolve which tumor-related signaling pathway played a key role by AEBP1 in BCa progression, the UniProt dataset was utilized and it was found that AEBP1 can interact with NF-κB, MAPK1/3 and PTEN (phosphatase and tensin homolog deleted on chromosome 10), which is also supported by the previous publications [17][18][19]. On the other hand, the TGF-β signaling pathway plays an indispensable role in the progression of BCa [20]. Western blotting was performed to measure the protein levels of p-Smad2, p-Smad3, Smad2/3, PTEN, p-AKT, AKT, p-NF-κB, NF-κB, p-ERK and ERK.…”
Section: Aebp1 Promoted Bca Progression By Activating Multiple Oncoge...mentioning
confidence: 61%
“…To resolve which tumor-related signaling pathway played a key role by AEBP1 in BCa progression, the UniProt dataset was utilized and it was found that AEBP1 can interact with NF-κB, MAPK1/3 and PTEN (phosphatase and tensin homolog deleted on chromosome 10), which is also supported by the previous publications [17][18][19]. On the other hand, the TGF-β signaling pathway plays an indispensable role in the progression of BCa [20]. Western blotting was performed to measure the protein levels of p-Smad2, p-Smad3, Smad2/3, PTEN, p-AKT, AKT, p-NF-κB, NF-κB, p-ERK and ERK.…”
Section: Aebp1 Promoted Bca Progression By Activating Multiple Oncoge...mentioning
confidence: 61%
“…For example, knockdown of 5-HT1B, Rh2, CCHa1-R , and fz in the developing Drosophila wing produced vein thickening phenotypes. The human orthologs for these genes, HTR1A, OPN4, GRPR , and FZD7 , respectively, have disease manifestations that increase metastasis, tumor cell growth, cell migration, and endothelial cell proliferation (Table 1) (Liu et al . 2022a; de Assis et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, knockdown of 5-HT1B, Rh2, CCHa1-R, and fz in the developing Drosophila wing produced vein thickening phenotypes. The human orthologs for these genes, HTR1A, OPN4, GRPR, and FZD7, respectively, have disease manifestations that increase metastasis, tumor cell growth, cell migration, and endothelial cell proliferation (Table 1) (Liu et al 2022a;de Assis et al 2021;Patel et al 2014;Zhang and Xu 2022). Similar vein thickening defects have been observed when knocking down the dSTIM gene, a calcium release-activated calcium (CRAC) channel (Eid et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer has surpassed lung cancer as the most common malignancy in the world . In particular, triple-negative breast cancer (TNBC) is the most challenging subtype of BC due to its high risk of recurrence and poor outcome. , With the success of tumor immunotherapy, BC has also entered an era of immunotherapy. The US Food and Drug Administration (FDA) has approved Atezolizumab and Keytruda for use in unresectable high-risk early, locally advanced, and metastatic TNBC. , Despite high mutation frequencies and PD-L1 expression in these subtypes, most patients remain unresponsive to ICB. , For instance, the response rate of PD-1 blockade in 170 patients with metastatic TNBC was only 4.7% .…”
mentioning
confidence: 99%
“…1 In particular, triplenegative breast cancer (TNBC) is the most challenging subtype of BC due to its high risk of recurrence and poor outcome. 2,3 With the success of tumor immunotherapy, BC has also entered an era of immunotherapy. The US Food and Drug Administration (FDA) has approved Atezolizumab and Keytruda for use in unresectable high-risk early, locally advanced, and metastatic TNBC.…”
mentioning
confidence: 99%